2003
DOI: 10.1038/sj.leu.2402745
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory analogs of thalidomide inhibit growth of Hs Sultan cells and angiogenesis in vivo

Abstract: We have previously shown that thalidomide and its potent immunomodulatory derivatives (IMiDs) inhibit the in vitro growth of multiple myeloma (MM) cell lines and patient MM cells that are resistant to conventional therapy. In this study, we further characterize the effect of these drugs on growth of B cell malignancies and angiogenesis. We established a beigenude-xid (BNX) mouse model to allow for simultaneous in vivo measurement of both anti-tumor and anti-angiogenic effects of thalidomide and its analogs. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 18 publications
3
71
0
4
Order By: Relevance
“…Preclinical studies in murine myeloma models confirm such a hypothesis. 39,40 These results assume greater importance with the targeted development of thalidomide analogs, and ongoing studies with other antiangiogenic agents in myeloma such as 2-methoxyestradiol and Bevacizumab. The significance of persistent blood vessels in the marrow is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies in murine myeloma models confirm such a hypothesis. 39,40 These results assume greater importance with the targeted development of thalidomide analogs, and ongoing studies with other antiangiogenic agents in myeloma such as 2-methoxyestradiol and Bevacizumab. The significance of persistent blood vessels in the marrow is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…102 ) than endothelial cell proliferation through the interference of PIk3/AKT signaling [128,129]. Finally, in pre-clinical in vivo mouse MM models both thalidomide and lenalidomide induced a significant reduction of tumor-associated MVD [130,131]. Although this evidence suggests that thalidomide and IMiDs have an anti-angiogenic activity, a reduction of MVD as well as VEGF levels is not always seen with thalidomide response in MM patients [100,125,127,132], suggesting that both the in vivo anti angiogenic effect of these drugs and the contribution of their antiangiogenic activity to the overall anti-tumor effect is uncertain.…”
Section: Anti Angiogenic Effect Of the Novel Anti-mm Agents And Futurmentioning
confidence: 99%
“…This is consistent with previous preclinical and clinical data, showing that thalidomide is less potent than IMiDs. [22][23][24][25][26][27] Pharmacokinetic studies from healthy volunteers and phase 1 trials of CC-4047 have shown that systemic levels between 1 M and 5 M are achievable (Dr David Stirling, Celgene, Warren, NJ; oral communication, October 5, 2005). In our study, significant inhibition of osteoclast formation was observed at concentrations of 1 M CC-4047.…”
Section: Discussionmentioning
confidence: 99%
“…on May 10, 2018. by guest www.bloodjournal.org From the in vitro and in vivo growth of MM cells. 22,23 In initial clinical phase 1 and 2 trials, single agent CC-4047 and CC-5013 in combination with dexamethasone achieved response rates of over 50% in relapsed and refractory MM. [24][25][26] We have shown that CC-4047 induces a shift in lineage commitment, resulting in increased myeloid cell development at the expense of erythroid cell commitment from human hematopoietic progenitors.…”
mentioning
confidence: 99%